Implementasi SI-LANCIP Dalam Layanan Publik Di Kota Palangka Raya - Christina, Meilianna Devita; Suprayitno; Ulfah, Sri Mujiarti (Laboratorium Administrasi Publik FISIP Universitas Andalas, 2025)
The emergence of Si-Lancip (Transportation Image Service System) in providing the best service to the community, especially in the transportation sector, is considered to make it very easy for the public to obtain public services. The aim of the research is to obtain a general overview regarding the implementation of Si-Lancip currently used by the Palangka Raya City Government. The research method used is descriptive qualitative. The findings of this research are the success of the implementation of Si-Lancip in realizing effective and efficient public services, so the Palangka Raya City Transportation Department created an innovation that can be used to serve the community, especially the transportation sector. Then the use of Si-Lancip has a positive impact on the community because the service becomes easier and faster and saves time for both employees of the Palangka Raya City Transportation Department and the community receiving the service